Analisis Prosedur Teknis Audit Investigasi Atas Indikasi Tindak Pidana Korupsi - Amril Arifin (Jurnal Ekonomika, 2013)
The aim of this research was to know whether the procedure of investigation audit technique was a tool in bringing corruptors to justice or only a tool in finding fraudulence in managing the state's finance. The method used in analyzing this research was a descriptive method which is collecting. The result of audit investigation, there is no space to make a small mistake would give meaningful impact for the next law process